Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Sure, let's calculate the matrix product [tex]\( AB \)[/tex] for the given matrices [tex]\( A \)[/tex] and [tex]\( B \)[/tex].
Given:
[tex]\[ A = \begin{bmatrix} 1 & 7 \\ -3 & 2 \end{bmatrix} \][/tex]
[tex]\[ B = \begin{bmatrix} 6 & 0 \\ 1 & -2 \end{bmatrix} \][/tex]
To find the product [tex]\( AB \)[/tex], we need to perform matrix multiplication. The element in the first row and first column of [tex]\( AB \)[/tex] is calculated by taking the dot product of the first row of [tex]\( A \)[/tex] and the first column of [tex]\( B \)[/tex]. Similarly, we will calculate the other elements.
1. Element (1,1) of [tex]\( AB \)[/tex]:
[tex]\[ (1 \times 6) + (7 \times 1) = 6 + 7 = 13 \][/tex]
2. Element (1,2) of [tex]\( AB \)[/tex]:
[tex]\[ (1 \times 0) + (7 \times -2) = 0 - 14 = -14 \][/tex]
3. Element (2,1) of [tex]\( AB \)[/tex]:
[tex]\[ (-3 \times 6) + (2 \times 1) = -18 + 2 = -16 \][/tex]
4. Element (2,2) of [tex]\( AB \)[/tex]:
[tex]\[ (-3 \times 0) + (2 \times -2) = 0 - 4 = -4 \][/tex]
Now, putting all these elements together, we get:
[tex]\[ AB = \begin{bmatrix} 13 & -14 \\ -16 & -4 \end{bmatrix} \][/tex]
So, the product [tex]\( AB \)[/tex] is:
[tex]\[ \begin{bmatrix} 13 & -14 \\ -16 & -4 \end{bmatrix} \][/tex]
Given:
[tex]\[ A = \begin{bmatrix} 1 & 7 \\ -3 & 2 \end{bmatrix} \][/tex]
[tex]\[ B = \begin{bmatrix} 6 & 0 \\ 1 & -2 \end{bmatrix} \][/tex]
To find the product [tex]\( AB \)[/tex], we need to perform matrix multiplication. The element in the first row and first column of [tex]\( AB \)[/tex] is calculated by taking the dot product of the first row of [tex]\( A \)[/tex] and the first column of [tex]\( B \)[/tex]. Similarly, we will calculate the other elements.
1. Element (1,1) of [tex]\( AB \)[/tex]:
[tex]\[ (1 \times 6) + (7 \times 1) = 6 + 7 = 13 \][/tex]
2. Element (1,2) of [tex]\( AB \)[/tex]:
[tex]\[ (1 \times 0) + (7 \times -2) = 0 - 14 = -14 \][/tex]
3. Element (2,1) of [tex]\( AB \)[/tex]:
[tex]\[ (-3 \times 6) + (2 \times 1) = -18 + 2 = -16 \][/tex]
4. Element (2,2) of [tex]\( AB \)[/tex]:
[tex]\[ (-3 \times 0) + (2 \times -2) = 0 - 4 = -4 \][/tex]
Now, putting all these elements together, we get:
[tex]\[ AB = \begin{bmatrix} 13 & -14 \\ -16 & -4 \end{bmatrix} \][/tex]
So, the product [tex]\( AB \)[/tex] is:
[tex]\[ \begin{bmatrix} 13 & -14 \\ -16 & -4 \end{bmatrix} \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.